1977
DOI: 10.1111/j.1365-2133.1977.tb14273.x
|View full text |Cite
|
Sign up to set email alerts
|

The long term treatment with B-carotene in erythropoietic protoporphyria: a controlled trial

Abstract: The efficacy of oral beta-carotene for the prevention of photosensitivity symptoms in erythropoietic protoporphyria was studied in a controlled cross-over trial in which it was compared with a placebo. No significant difference was found between the 2 preparations. Patients' symptoms showed statistically significant association with sunlight hour records.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 7 publications
(4 reference statements)
0
31
0
Order By: Relevance
“…Treatment of the painful photosensitivity, mediated by the excess of protoporphyrin IX, is difficult. β‐carotene was found to be no more effective than placebo in a randomized controlled trial (RCT), and in practice, few patients with EPP find the treatment worthwhile . NB‐UVB has yet to be assessed formally in the treatment of EPP (or XLDPP), although anecdotal evidence suggests that it may be of benefit .…”
Section: Reportmentioning
confidence: 99%
“…Treatment of the painful photosensitivity, mediated by the excess of protoporphyrin IX, is difficult. β‐carotene was found to be no more effective than placebo in a randomized controlled trial (RCT), and in practice, few patients with EPP find the treatment worthwhile . NB‐UVB has yet to be assessed formally in the treatment of EPP (or XLDPP), although anecdotal evidence suggests that it may be of benefit .…”
Section: Reportmentioning
confidence: 99%
“…Increase of UV tolerance was seen in 84% of 133 patients taking betacarotene with a starting dose of 15 mg/day to 180 mg/day [27]. Whereas in a controlled, cross-over trial in 14 patients suffering from erythropoietic protoporphyria no significant difference was found between betacarotene (100 mg/day) and placebo [28].…”
Section: Betacarotenementioning
confidence: 92%
“…However, another study on 23 healthy volunteers showed no statistically significant carotenoid‐dependent photoprotection against UVA‐, UVB‐ or PUVA‐induced erythema, and also no decrease in UVB‐induced DNA damage 28 . The only controlled trial of β‐carotene in the treatment of EPP showed no significant improvement over placebo 29 but this study was subsequently criticised for possible under‐dosage with β‐carotene. This was unfortunate, as high‐dose β‐carotene has been demonstrated to be safe and well‐tolerated 30 .…”
Section: Treatment Of Photosensitivitymentioning
confidence: 95%